A numerical approach for optimal control model of the convex semi-infinite programming - Hamid Rouhparvar (Iranian Journal of Optimization, 2015)
In this paper, convex semi-infinite programming is converted to an optimal control model of neural networks and the optimal control model is solved by iterative dynamic programming method. In final, numerical examples are provided for illustration of the purposed method.